Diabetic Retinopathy May Indicate an Increased Risk of Cardiovascular Disease in Patients With Type 1 Diabetes—A Nested Case-Control Study in Brazil - Melo, Laura Gomes Nunes; Morales, Paulo Henrique; Drummond, Karla Rezende Guerra; Santos, Deborah Conte; Pizarro, Marcela Haas; Barros, Bianca Senger Vasconcelos; Mattos, Tessa Cerqueria Lemos; Pinheiro, André Araújo; Mallmann, Felipe; Leal, Franz Schubert Lopes; Muniz, Luiza Harcar; Malerbi, Fernando Korn; et al. (Frontiers in Endocrinology, 2019)
Objective: Cardiovascular disease, the leading cause of death worldwide, and diabetic retinopathy, the main cause of blindness in economically active populations, share clinical risk factors and pathophysiological features. The aim of this study is to examine the association between diabetic retinopathy, cardiovascular disease, and common risk factors in patients with type 1 diabetes. Design and Methods: This nested case-control study was performed in patients from the Brazilian Type 1 Diabetes Study Group, a nationwide survey that was conducted in Brazil that enrolled 1760 patients with type 1 diabetes. A total of 342 patients were selected (57 cases with macrovascular disease and 285 controls who were matched for duration of diabetes and gender). Results: In the exploratory analysis, stratified by cardiovascular disease, the following variables were statistically significant: age (p=0.037), hypertension (p=0.035), high BMI (p=0.046), diabetic retinopathy (p=0.003), and chronic kidney disease (p=0.026). By multivariate logistic regression, patients with diabetic retinopathy were more likely to develop cardiovascular disease (OR 2.16, 95% CI 1.16-4.02, p=0.015). Although to a lesser extent than diabetic retinopathy, higher BMI levels were also related to an increase in the risk of cardiovascular disease of 1.08 (95% CI 1.01-1.15, p=0.024). Conclusion: The presence of diabetic retinopathy indicates a greater risk for cardiovascular disease in Brazilian patients with type 1 diabetes. Further studies are warranted to determine whether a noninvasive exam, such as fundoscopy, could help identify patients who show an increased risk for cardiovascular disease.